Requirements of Energy and Protein for Arabic Chicken During Early Egg Production - Syafwan; Noferdiman (Faculty of Animal Science, Bogor Agricultural University, 2020)
The objectives of this experiment were to calculate energy (ME) and crude protein (CP) requirements of Arabic chicken hens in the tropical climates during the early laying period by a choice feeding method. One hundred and thirty-eight of 22-week old Arabic chicken hens were allotted into 12 sheltered pens with 10-14 chicks each. The no free-choice group hens fed a standard diet conforming with the Hy-line Brown Commercial Management Guide, whilst the free-choice group hens fed with a standard diet, an energy-protein rich diet, an energy-rich diet, a protein-rich diet, and an energy-protein poor diet. Feed consumption, energy and protein consumptions, energy (kcal of ME/kg) and protein (g of CP/kg) dietary concentrations were recorded weekly, and egg production was recorded daily. All performance data were taken repeatedly during the first 28 weeks of egg production and were analyzed after summarizing weekly data into seven 28-d periods using the Mixed Procedure in SAS. The dietary treatments had no clear effect on feed and protein consumption but had a significant effect on energy consumption, energy and protein concentrations, and egg production. Energy consumption of the no free-choice group hens was lower than those in the free-choice group hens (1580 vs. 1718 kcal of ME/kg/hen; p<0.05). Energy and protein concentration in the diet of the no free-choice group hens were lower (p<0.01) than those in the free-choice group hens (2814 vs. 3050 kcal of ME/kg and 184 vs. 189 g of CP/kg, respectively). The no free-choice group produced less egg (p<0.01) than those of the free-choice group (56% vs. 61%). Arabic chicken hens consumed more feed from an energy-protein rich diet and an energy-rich diet and consumed less feed from a protein-rich diet and an energy-protein poor diet. Based on the choice feeding, ME and CP requirements for Arabic chicken hens during early egg production were higher than ME and CP contained in the control diet. An average hen day production was higher in the free choice group compared to the control diet group.